Kayam, Umar, Sri Sumarah, Evi Luliana Siregar y Atzimba Luna Becerril (trad.), México, El Colegio de México, Centro de Estudios de Asia y África, 2008, 86 pp. - Urrutia, Elena (Estudios de Asia y África, 2009)
Kayam, Umar, Sri Sumarah, Evi Luliana Siregar y Atzimba Luna Becerril (trad.), México, El Colegio de México, Centro de Estudios de Asia y África, 2008, 86 pp.